Supercritical Fluid Technology: A Review - Parhi Rabinarayan; Suresh Padilama (Journal of Advanced Pharmaceutical Science And Technology, 2013)
The challenges ever faced by pharmaceutical industry is mainly due to discovery of new drugs and development of new technologies. Supercritical fluid (SCF) technology is one such technique, which has become an important tool in the production of different particulate systems along with extraction and drying of protein and peptides during last couple of decade because of its specific properties such as flexibility in use, reduced environmental concern and its simplicity. In this review, we briefly describe the operating principles and parameters influencing each one of SCF processes along with their merits and perspectives. The application of SCF technology in pharmaceutical industry, including particle and crystal engineering, composite particles’ preparation, coating of solid dosage form, liposome preparation, extraction and protein and peptide drying are discussed.
Keywords: Supercritical fluid